2010
DOI: 10.1680/geot.9.p.109
|View full text |Cite
|
Sign up to set email alerts
|

Soil–environment interactions in geotechnical engineering

Abstract: The range of problems that geotechnical engineers must face is increasing in complexity and scope. Often, complexity arises from the interaction between the soil and the environment – the topic of this lecture. To deal with this type of problem, the classical soil mechanics formulation is progressively generalised in order to incorporate the effects of new phenomena and new variables on soil behaviour. Recent advances in unsaturated soil mechanics are presented first: it is shown that they provide a consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
198
0
20

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(237 citation statements)
references
References 231 publications
3
198
0
20
Order By: Relevance
“…Nevertheless, numerous forensic analyses of geotechnical problems related to slope stability (Griffiths and Lu 2005;Gens 2010;Sorbino and Nicotera 2013), foundations on expansive soils (Attwooll et al 2006), settlement of railway embankments (Cardoso et al 2012) and problems related to geo-environmental engineering and mining engineering have provided some insight on engineering applications of unsaturated soil mechanics. For example, Alonso and Olivella (2006) reported that embankments and dams can experience significant deformations under the influence of seasonal wetting and drying cycles.…”
Section: Final Notementioning
confidence: 99%
“…Nevertheless, numerous forensic analyses of geotechnical problems related to slope stability (Griffiths and Lu 2005;Gens 2010;Sorbino and Nicotera 2013), foundations on expansive soils (Attwooll et al 2006), settlement of railway embankments (Cardoso et al 2012) and problems related to geo-environmental engineering and mining engineering have provided some insight on engineering applications of unsaturated soil mechanics. For example, Alonso and Olivella (2006) reported that embankments and dams can experience significant deformations under the influence of seasonal wetting and drying cycles.…”
Section: Final Notementioning
confidence: 99%
“…The main part of their research was focused on a bentonite, yielding large deformations (up to 15% due to a change in pore liquid only). Constitutive models based on these results were proposed by Loret et al (2002), Gajo & Loret (2003), and Gajo et al (2002) under one framework, and by Gens (2010) and Guimarães et al (2007) under a different framework.…”
Section: Theories and Evidencementioning
confidence: 99%
“…In contrast, the latter framework (Gens, 2010;Guimarães et al, 2007) consists of a double-structured model in which the chemical part is represented by osmotic suction. This osmotic suction works at the microscopic level, and all of the strains it produces are considered completely reversible.…”
Section: Theories and Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…interventions on near-surface and/or underground deposits for the purpose of environmental remediation (e.g., disposal of CO 2 and hazardous wastes) and risk management (e.g., protection of cities and/or coastal areas from sea level rise and other geohazards). Research on the multi-physics of geological systems, as well as on the couplings between mechanical, hydrologic, chemical and biological agents in the natural environment, is therefore a new frontier to be explored to devise innovative technological solutions able to face the abovementioned challenges [4].…”
Section: Introductionmentioning
confidence: 99%